Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar - Kullander, Sven O.; Norén, Michael (Zootaxa, 2016)
Danio htamanthinus, new species, is described from small streams in the vicinity of Htamanthi on the middle Chindwin River. It is most similar to D. choprae and D. flagrans from the Ayeyarwaddy River drainage, sharing the same elaborate colour pattern with dark vertical bars and a red interstripe along the posterior side, but is distinguished by the absence of a P+1 stripe and presence of a P stripe represented only by small spots. The uncorrected p-distance in the mitochondrial COI gene separates D. htamanthinus from D. choprae by 4.3% and from D. flagrans by 7.5%. The largest specimen is only 22.9 mm in standard length (male holotype), but the holotype and one other male, 19.5 mm SL, feature sex-specific pectoral-fin tubercles, and a female as small as 16.6 mm SL has ripening ova. In a phylogenetic analysis based on COI sequences, D. htamanthinus is sister taxon of D. flagrans+D. choprae, and those three species are sister group of D. margaritatus+D.erythromicron.